Implementasi Model Pembelajaran INoSIT untuk Meningkatkan Kompetensi Literasi Sains Peserta Didik SMPN 4 Kendari - Takda, Amiruddin; Galib, La Maronta; Munir, Asmawati; Sappaile, Pallawagau (Jurnal Penelitian Pendidikan Fisika, 2021)
The research objective was to determine the effectiveness of INoSIT (Integrated Nature of Science Inquiry with Technology) learning model to improve the scientific literacy competence of class IX2 students of SMPN 4 Kendari. Through the design of one group pretest-posttest which involved three science teachers as model teacher and observers which were carried out in odd semesters of the 2019/2020 school year. Data collection used the observation sheet for the implementation of learning, student activities, science literacy tests and student response questionnaires. The results of the analysis of average n-gain mean on scientific literacy competence were obtained on the indicators explaining scientific phenomena that were in the high category; while indicators evaluate and design scientific inquiry and interpretation of data and scientific evidence are still in the medium category. Furthermore, the results of hypothesis testing show that there is a significant difference between the scientific literacy competencies of students through the pretest and posttest on . In conclusion, the implementation of the INoSIT learning model in science learning is effective in increasing the scientific literacy competence of class IX2 students of SMPN 4 Kendari.